Gamma interferon is a major mediator of antiviral defense in experimental measles virus-induced encephalitis. - Finke, D (1995)
Measles virus infection of the central nervous system in the murine model of experimental measles virus-induced encephalitis is successfully controlled by virus-specific T-helper lymphocytes. T cells from BALB/c mice that are resistant to measles virus encephalitis proliferate well against measles virus in vitro, and bulk cultures recognize viral nucleocapsid and hemagglutinin as well as fusion proteins. The measles virus-specific T cells secrete large amounts of interleukin 2 (IL-2), gamma interferon (IFN-gamma), and tumor necrosis factor alpha (TNF-alpha) but no IL-4, IL-6, or IL-10, and hence the cytokine pattern is consistent with that of subtype 1 T-helper lymphocytes. In contrast, cells obtained from measles virus-infected susceptible C3H mice recognize measles virus proteins only weakly and secrete little IFN-gamma and TNF-alpha. Treatment of infected mice with anti-TNF-alpha antibodies has no effect on survival or virus clearance from the brain. Upon neutralization of IFN-gamma in vivo, the phenotype of measles virus-specific T-helper cells isolatable from BALB/c mice is reversed from subtype 1 to subtype 2-like. Anti-IFN-gamma antibody-treated BALB/c mice are susceptible to measles virus encephalitis, and viral clearance from the central nervous system is impaired. These results indicate that IFN-gamma plays a significant role in the control of measles virus infection of the central nervous system.